2019
DOI: 10.1158/0008-5472.can-19-0076
|View full text |Cite
|
Sign up to set email alerts
|

LINE-1 Retrotransposition Promotes the Development and Progression of Lung Squamous Cell Carcinoma by Disrupting the Tumor-Suppressor Gene FGGY

Abstract: Somatic long interspersed element-1 (LINE-1) retrotransposition is a genomic process that relates to gene disruption and tumor occurrence. However, the expression and function of LINE-1 retrotransposition in lung squamous cell carcinoma (LUSC) remain unclear. We analyzed the transcriptomes of LUSC samples in The Cancer Genome Atlas and observed LINE-1 retrotransposition in 90% of tumor samples. Thirteen LINE-1 retrotranspositions of high occurrence were identified and further validated from an independent Chin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 59 publications
(55 reference statements)
1
42
0
Order By: Relevance
“…In colon cancer, Miki et al reported that LINE-1 insertion disrupts the tumor suppressor gene APC, which can lead to gene inactivation (Miki et al, 1992). In lung squamous cell carcinoma, we found that LINE-1 insertion into tumor suppressor gene FGGY promotes cell proliferation and invasion in vitro, and facilitates tumorigenesis in vivo (Zhang et al, 2019).…”
Section: Line-1 Integrations and Cancermentioning
confidence: 90%
See 3 more Smart Citations
“…In colon cancer, Miki et al reported that LINE-1 insertion disrupts the tumor suppressor gene APC, which can lead to gene inactivation (Miki et al, 1992). In lung squamous cell carcinoma, we found that LINE-1 insertion into tumor suppressor gene FGGY promotes cell proliferation and invasion in vitro, and facilitates tumorigenesis in vivo (Zhang et al, 2019).…”
Section: Line-1 Integrations and Cancermentioning
confidence: 90%
“…It was reported that LINE-1 insertions in the FGGY gene can upregulate cytochrome P450, arachidonic acid metabolism, and glycerolipid metabolism. These metabolic disorders can lead to the occurrence of a variety of diseases and poor prognosis (Zhang et al, 2019).…”
Section: Line-1 and Metabolic Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…The Table 3 shows the hotpots for the rest of cancer types and the complete list is shown in Supplementary Table 1. This is interesting because it highlights genes not well studied such as NBPF12 in BRCA, LPAR6 or ASXL2 in BLCA, and FGGY in LUSC, which is being studied recently [41].…”
Section: Hotspots Across Cancer Typesmentioning
confidence: 95%